O front-end of innovation em sistemas produto-serviço em empresas fabricantes de equipamentos médico-hospitalares: análise do processo de decisão - Braga, Francisco Andrea Simões (2019)
Product-Service System (PSS) corresponds to an integrated series of products and services to the customer and an approach that, besides innovating in the generation of customer value, can bring benefits from the environmental point of view. The PSS list has been presented to a large number of companies, including manufacturers of hospital equipment, who have been able to develop products, services and solutions that enhance quality and reduce healthcare costs. However, the methodologies for the development of PSS are dependent on models, methods and tools for other areas of research. The challenge is how the specificities of development, in addition to monitoring the decision-making process of the pre-development phase. In view of this context, this paper aims to describe and analyze how the information and evaluation criteria of innovation of two companies in the health sector to care for children. The bibliographic research and the case study were applied. There are three results of the research results. The results of the processes of generation and systematization in the execution of the processes and decisions in the front end of the innovation of the process of development of the PSS. Second, there was a lack of integration between product development and service activities. Third, they are important and current statistics on the part of the companies investigated. The implications of this dissertation proposal are: (i) proposal of a framework for the decision-making process in the front-end of innovation of the development of the PSS in companies manufacturing medical-hospital equipment; (ii) impressive, companies that are part of the quality sector of their decision-making processes.